Effect of load stress ratio on nominal and effective notch fatigue strength assessment of HFMI-treated high-strength steel cover plates. (October 2020) - Leitner, Martin; Stoschka, Michael
Highlights: Effect of stress ratio on the fatigue strength of welded and HFMI-treated steel joints. Applicability study of the IIW recommendations for the HFMI treatment. Fatigue assessment based on nominal and effective notch stress approach. Abstract: The International Institute of Welding published IIW-recommendations for the HFMI-treatment, which covers fatigue assessment procedures and quality assurances guidelines. This paper contributes to the validation of the detrimental effect of high R-ratios on HFMI-treated cover plate specimens made of high-strength steel S700. Applying the nominal stress approach, the recommended S/N-curves agree well to the experiments in both cases, R = 0.1 and R = 0.5. In case of the effective notch stress approach, only for R = 0.1 a sound agreement is observed, whereas for R = 0.5 a more pronounced reduction of the fatigue strength may be considered within the recommendations to ensure an overall conservative assessment.